Nasal Methicillin-Resistant S. Aureus is a Major Risk for Mediastinitis in Pediatric Cardiac Surgery - Katayanagi, Tomoyuki (Annals of Thoracic and Cardiovascular Surgery, 2015)
Background: Mediastinitis caused by methicillin-resistant Staphylococcus aureus (MRSA) is a serious complication after pediatric cardiac surgery. An outbreak of surgical site infections (SSIs) provided the motivation to implement SSI prevention measures in our institution.Methods: Subjects comprised 174 pediatric patients who underwent open-heart surgery after undergoing preoperative nasal culture screening. The incidence of SSIs and mediastinitis was compared between an early group, who underwent surgery before SSI measures (Group E, n = 73), and a recent group, who underwent surgery after these measures (Group R, n = 101), and factors contributing to the occurrence of mediastinitis were investigated.Results: The incidence of both SSIs and Mediastinitis has significantly decreased after SSI measures. With regard to factors that significantly affected mediastinitis, preoperative factors were “duration of preoperative hospitalization” and “preoperative MRSA colonization,” intraoperative factors were “Aristotle basic complexity score,” “operation time,” “cardiopulmonary bypass circuit volume” and “lowest rectal temperature.” And postoperative factor was “blood transfusion volume.” Patients whose preoperative nasal cultures were MRSA-positive suggested higher risk of MRSA mediastinitis.Conclusions: SSI prevention measures significantly reduced the occurrence of SSIs and mediastinitis. Preoperative MRSA colonization should be a serious risk factor for mediastinitis following pediatric cardiac surgeries.